2006
DOI: 10.1016/j.ejcts.2006.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac transplantation following ACORN CorCap device implantation

Abstract: Passive ventricular restraint devices, such as the ACORN CorCap, have been introduced as a potential therapy for congestive heart failure (CHF). These mesh devices act as a mechanical support for the dilated heart. Due to incorporation of the device to the epicardium, concerns about the feasibility of reoperation following CorCap placement have been raised. This case illustrates that although technically challenging, reoperation for heart transplantation after CorCap implantation is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Upon dilation the radius of the ventricle wall increases, thus to maintain the same pressure inside the injured ventricles during ejection as an uninjured heart, the tension consequently increases. Different approaches have previously been suggested: restraints could serve either as a ''wrap'' for both ventricles, [35,36] solely for the left ventricle, [37] or as described here, as a patch which covers only the infarcted area. [38] The fact that the biomaterial investigated in this paper is stiffer than the myocardium itself (0.14 and 0.2-0.5 MPa for myocardium of rat and human, respectively, compared to 24.6 MPa for PET/DLA-0.2 wt%TiO 2 ) indicates that it will support the heart and prevent dilation.…”
Section: Resultsmentioning
confidence: 99%
“…Upon dilation the radius of the ventricle wall increases, thus to maintain the same pressure inside the injured ventricles during ejection as an uninjured heart, the tension consequently increases. Different approaches have previously been suggested: restraints could serve either as a ''wrap'' for both ventricles, [35,36] solely for the left ventricle, [37] or as described here, as a patch which covers only the infarcted area. [38] The fact that the biomaterial investigated in this paper is stiffer than the myocardium itself (0.14 and 0.2-0.5 MPa for myocardium of rat and human, respectively, compared to 24.6 MPa for PET/DLA-0.2 wt%TiO 2 ) indicates that it will support the heart and prevent dilation.…”
Section: Resultsmentioning
confidence: 99%
“…We deliberately wanted to avoid the dense adhesions of the CorCap™, which is an artificial material that fixes firmly to the heart and surrounding tissues. The hazards of reoperating on a patient with a previously placed CorCap™ was well described by Schroder and colleagues during the cardiectomy of the recipient at the time of transplantation [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The literature is nearly devoid of information related to patients undergoing subsequent cardiac surgery procedures in the setting of a CorCap™ prosthesis. The only reference to a CorCap™ patient undergoing a second cardiac surgery is by Schroder et al who described a man with IDCM who underwent cardiac transplantation following a CorCap™ implantation two years earlier 5 . Schroder et al case was notable for dense adhesions surrounding the CorCap™ device along the lateral aspect of the left ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Postcardiectomy examination of the native heart revealed that the dense adhesions caused by the device resulted in the fusion of the epicardium, the CorCap™ device, and the pericardium. A plane between the device and the pericardium could not be established without possible injury to the phrenic nerve—as such, an altered technique for the cardiectomy was necessary and was prolonged (three hour); significant microvascular bleeding was encountered and multiple transfusions were necessary 5 …”
Section: Discussionmentioning
confidence: 99%